Relationships between Population and Habitat Characteristics and Reproduction of the Rare Gentiana pneumonanthe L. - J. Gerard B. Oostermeijer; Sheila H. Luijten; Zdenka V. Křenová; Hans C. M. Den Nijs (Conservation Biology, 1998)
We investigated the relationships among a number of population and site characteristics and the ovule and seed production and seed set in 17 populations of the rare, self‐compatible, bumblebee‐pollinated perennial Gentiana pneumonanthe L. in the Netherlands. Population size and offspring heterozygosity were used as population properties; grass and heath cover, soil concentrations of various ions, soil acidity (pH), and soil moisture were used as habitat characteristics. Our aim was to find out how important population size and genetic variation are for the seed production of a rare plant, when accounting for a number of habitat parameters that might also be important for successful reproduction. Correlation coefficients between population and habitat characteristics showed that sites with low soil moisture and higher concentrations of most nutrients have a higher cover of grasses and a low cover of heath species. At such sites the population size of G. pneumonanthe was small and offspring heterozygosity was low. The number of ovules per fruit (a component of reproductive effort) was negatively associated with heterozygosity, phosphorus, and pH and positively associated with calcium, potassium, SO 4 , NH 4 , and electric conductivity. Total vegetation cover correlated positively with the variation in ovule production among individuals. Seed set and number of viable seeds per fruit, indicators of the success of fertilization and seed maturation, correlated positively with population size, the cover of co‐flowering heath species, and the same group of nutrients that (independently) had a positive effect on ovule production. A high NO 2 concentration might be toxic because it had a negative effect on the number of viable seeds. Seed weight seemed to be independent of any population or habitat parameter. Besides lower mean values, we also found more variation in reproductive success among individuals in smaller populations. We conclude that plants in small populations of G. pneumonanthe have a similar reproductive potential per flower but have lower seed production and a higher uncertainty of successful reproduction than plants in large populations. Genetic variation was apparently not very important. In addition to population size, habitat characteristics also seemed to be important for seed production and seed set. The most important factors were the facilitating effect of the presence of other insect‐pollinated species and the concentrations of specific nutrients in the soil. To restore small populations, we advise small‐scale sod cutting around the remaining reproductive individuals. This simultaneously allows germination and seedling establishment of G. pneumonanthe , removes soil nutrients, and restores the cover of pollinator‐attracting heath species at the cost of grasses. Relaciones entre Características Poblacionales y del Habitat y la Reproducción de la Especie Rara Gentiana pneumonanthe L. Investigamos las relaciones entre un número determinado de características poblacionales y de sitio y la producción de óvulos y semillas en 17 poblaciones de la especie de hierba rara, autocompatible, polinizada por abejas y perenne Gentiana pneumonanthe L. en los Países Bajos. Utilizamos el tamaño poblacional y la heterocigosidad de la progenie como propiedades poblacionales, la cobertura de gramíneas y ericáceas en Ia vegetación y la concentración de algunas sustancias nutritivas en el suelo fueron usadas como características bióticas y abióticas del hábitat. Nuestra meta fue la de encontrar que tanta importancia tienen el tamaño poblacional y la variación genética en la producción de semillas de una planta rara, tomando en consideración un número de parámetros del hábitat que pueden ser importantes para una reproducción exitosa. Los coeficientes de correlación entre las características poblacionales y del hábitat mostraron que los sitios con grado de humedad bajo y concentraciones de nutrientes altas tienen una cobertura de grarmíneas elevada y de ericáceas reducida. En tales sitios, el tamaño poblacional de G. pneumonanthe es más pequeño y la heterocigosidad de las progenies es más baja. La producción potencial de semillas (medida en forma de número de óvulos por fruto) tenía una relación negativa con la heterocigosidad, la concentración de P y el pH del suelo y una relación positiva con las concentraciones de Ca, K, SO 4 y NH 4 y la conductividad eléctrica. Se encontró una correlación positiva entre la variación del número de óvulos y la cobertura total de la vegetación. El éxito de la fecundación y la maduración de semillas estuvo correlacionado positivamente con el tamaño poblacional, la cobertura de las ericáceas (que florecen simultáneamente) en la vegetación y el mismo grupo de nutrientes que (independientemente) surtían efecto positivo en el número de óvulos. La concentración de NO 2 en el suelo mostró una correlación negativa con el número de semillas viables. También Ia variación en el éxito reproductivo fue más alta en las poblaciones pequeñas. No se encontró relación significativa entre el peso de las semillas y alguna de las características de la población o del hábitat. En base a relaciones observadas, concluimos que las poblaciones pequeñas de Gentiana pneumonanthe tienen el mismo potencial reproductivo por flor, pero tienen una menor producción de semillas y una mayor incertidumbre reproductiva en comparación con las poblaciones grandes. Los factores importantes para el éxito reproductivo son el tamaño poblacional, el efecto facilitador de la presencia de otras especies de hierbas polinizadas por insectos y la disponibilidad de sustancias nutritivas específicas en el suelo. Recomendamos la eliminación en pequeña escala del césped en los alrededores de los adultos reproductivos remanentes para restaurar pequeñas poblaciones. Este método hace posible al mismo tiempo la germinación y el establecimiento de individuos nuevos, remueve nutrientes del suelo y restablece la covertura de especies atrayentes de polinizadores.